2020
DOI: 10.1007/s00422-020-00815-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishing metrics and control laws for the learning process: ball and beam balancing

Abstract: Understanding how dexterity improves with practice is a fundamental challenge of motor control and neurorehabilitation. Here we investigate a ball and beam implementation of a dexterity puzzle in which subjects stabilize a ball at the mid-point of a beam by manipulating the angular position of the beam. Stabilizability analysis of different biomechanical models for the ball and beam task with time-delayed proportional-derivative feedback identified the angular position of the beam as the manipulated variable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…No significant changes were observed on the parameters over the trials implying that the identified feedback mechanism has been already learned and practiced before during the activities of daily living. The effect of learning process is more pronounced when a new and unknown task is to be performed, e.g, ball-and-beam balancing 45 , balancing on balance board 54 , beam walking 55 or combined quiet standing and stick balancing 28 . A question arises whether practice or other techniques can be developed to further improve the performance against sudden perturbations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant changes were observed on the parameters over the trials implying that the identified feedback mechanism has been already learned and practiced before during the activities of daily living. The effect of learning process is more pronounced when a new and unknown task is to be performed, e.g, ball-and-beam balancing 45 , balancing on balance board 54 , beam walking 55 or combined quiet standing and stick balancing 28 . A question arises whether practice or other techniques can be developed to further improve the performance against sudden perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Lighter shaded region to the right of the dashed line is associated with Im(λ 1 ) > 0 and the corresponding solution component reads B 1 e λ 1 t +B 1 eλ 1 t , which is oscillatory with angular frequency Im(λ 1 ) (hereλ 1 andB 1 are the complex conjugate of λ 1 and B 1 , respectively). The black-green dashed line is called node-spiral separation line since it separates node type and spiral type solutions 45 . Note that the point (p * , d * ) corresponding to the fastest response lies on the node-spiral separation line.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the model of the human body and the operation of the CNS involve many uncertain parameters, it is advantageous to consider tasks associated with low-degree-of-freedom mechanical models with well-defined physical properties. For instance, stick balancing [4,6,11,16], ankle strategy during quiet standing [5,9,15,17,18] and ball and beam balancing [19] are often modelled as a single inverted pendulum system, while ankle-hip strategy during quiet standing [20,21] and standing on a balance board [22][23][24] are modelled as a generalized double inverted pendulum.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the CNS can be analyzed by performing simple balancing tasks that can be described by lowdegree-of-freedom mechanical models. For example, stick balancing [9][10][11], ankle strategy during quiet standing [12][13][14][15] and ball and beam [16] balancing are often modelled as a single-segment single-joint inverted pendulum, while hip strategy during quiet standing [17][18][19] and standing on a balance board [20][21][22] are modelled as a system of double inverted pendulum.…”
Section: Introductionmentioning
confidence: 99%